Business Opportunity: NIMS Crispy Choco Tub / Amalin Aliesya Mohd Azmi - Mohd Azmi, Amalin Aliesya (2021)
I would like to thanks all my friends, my loving family and lectures for helped me complete my assignment fundamentals of entrepreneurship (ENT 300) which is called as business opportunity. Also, thanks a lot Madam Hazelen who given me guidance to complete my second assignment. For this project, I sold NIMS Crispy Choco Tub products because it is my favourite snack in flavour chocolate, it helps to relieve stress and we can eat while doing assignment or watching movies. Before start approach these products, I started discovery and search for business opportunities. Opportunity is defined as a situation that enables an entrepreneur to offer marketable products or services to interested buyers and end users. As a student, I sold NIMS Crispy Choco Tub because it worth and affordable price for students like me. Alhamdulillah, by slowly start sell NIMS Crispy Choco Tub products to my family and friends in university who never stop supporting me in my business. I sold this NIMS Crispy Choco Tub using the promotion method such as WhatsApp group, social media and websites. Thankfully, I realized that it had reached my target of RM300.00. In the business, I learn that creative thinking skills, knowledge and motivation is important for doing business. As a creative entrepreneur, we must to be a risk taker to challenge ourselves fear of failure in business. Otherwise, I figure out that communication skills with customer have being improved and experiencing how to handle business properly.